IMPROVING ETAWAH CROSSBREED GOATS MILK PRODUCTION AND QUALITY WITH LIQUID SMOKE FEED BLOCKS DIETARY SUPPLEMENTATION - Tutik Lusyta Aulyani; Andy; Arwan; Imran; Irma; Sri Wahyuni (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Improving the productivity and milk quality of Etawah Crossbreed (PE) goats remains a challenge due to limited use of feed supplements that effectively support lactation performance. Liquid smoke contains antibacterial and antioxidant compounds that may enhance rumen fermentation when incorporated into block feed. This study aimed to evaluate the effects of liquid-smoke feed blocks dietary supplementation on feed intake, milk yield, and milk quality of lactating PE goats, as assessed by specific gravity, protein, fat, and lactose. This research using a Latin Square Design, with three PE goats were used in each treatment consisting of P0 (control), P1 (1% liquid-smoke block feed), and P2 (2% liquid-smoke block feed) and the experiment lasted nine weeks.. Results showed that block feed supplementation did not affect forage intake, which remained between 2.31–2.41 kg/head/day. Milk yield increased significantly in P1 and P2 compared to P0, with the highest production observed in P1 (773.81 ml/head/day). Milk quality parameters were not significantly affected by treatments, although all values remained within normal ranges. Based on research results, can be concluded that liquid-smoke block feed effectively improves milk yield without compromising milk quality in PE goats. Further studies with longer experimental periods are recommended to observe milk quality.